A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMA NEGERI 2 BANGKINANG IN COMPREHENDING ENGLISH TEXTS - Santri Utami ms; Fadly Azhar; Eliwarti Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The main objective of this descriptive research was to find out about students’ ability in comprehending English texts. The sample of this research was the second year students of SMAN 2 Bangkinang. There were 52 students participating as the sample of this research.Tthe instrument of the research was a set of multiple choice test which consist of 48 questions regarding the reading components and The data were quantitative. The data were analyzed by calculating the score of the students in answering the test and classifying them to a certain level of ability using Harris formula. The results were that out of 52 students, no one student (0%) in excellent level of ability, 16 students (30.77%) were in good level of ability, 17 students (32.69%) were in average level of ability, and for the most part, 19 students (36.54%) were in poor level of ability. In addition, the average score of the students in comprehending English texts was 51.80. It meant that the students’ ability in comprehending English texts was in the average level of ability. The most difficult aspect is the students’ ability in finding inference with mean score 42.9 was in poor level of ability. This research recommended the students to to do more practice in reading three kinds of text (Narrative, Report and analytical exposition texts) in order to comprehend texts. Further research can focus on studying each subtopic in details. Other researchers can also focus on how to overcome the high level of difficulties in comprehending English texts, particular in finding inferences.Keywords: Ability, Comprehending, English texts